PENGARUH KOMITMEN PROFESIONAL DAN KEYAKINAN TERHADAP HUKUM KARMA PADA KEPUTUSAN ETIS KONSULTAN PAJAK DI PROVINSI BALI - Trisna Windika Pratiwi; Kadek Dewi Padnyawati (Jurnal Widya Akuntansi dan Keuangan, 2022)
An ethical decision is a decision that must be made by every professional who serves a particular field of work. The purpose of this study is to obtain empirical evidence regarding the effect of professional commitment and belief in the law of karma on tax consultant ethical decisions. The sampling method used in this research is nonprobability sampling method with saturated sampling technique, so that the number of samples used in this study is 102 tax consultants registered in Bali Province. The analysis technique of this research uses multiple linear regression analysis. The results showed that each of the independent variables of the study, namely professional commitment and belief in the law of karma, had a positive effect on the tax consultant's ethical decisions